2021
DOI: 10.3390/e23081015
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Strange Star in 5D Einstein-Gauss-Bonnet Gravity

Abstract: In this paper, we investigated a new anisotropic solution for the strange star model in the context of 5D Einstein-Gauss-Bonnet (EGB) gravity. For this purpose, we used a linear equation of state (EOS), in particular pr=βρ+γ, (where β and γ are constants) together with a well-behaved ansatz for gravitational potential, corresponding to a radial component of spacetime. In this way, we found the other gravitational potential as well as main thermodynamical variables, such as pressures (both radial and tangential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…Spherical symmetry, cylindrical symmetry and hyperbolic systems have been studied in various treatments [6][7][8][9][10][11][12][13][14][15][16][17][18]; this emphasizes the role of complexity in various geometries. It is interesting to note that issues related to complexity have been investigated in generalised gravity theories including Einstein-Gauss-Bonnet theory, the more general Lovelock theory, f(R) theory and other extended theories of gravity [6,[19][20][21][22][23][24].…”
Section: Previous Workmentioning
confidence: 99%
“…Spherical symmetry, cylindrical symmetry and hyperbolic systems have been studied in various treatments [6][7][8][9][10][11][12][13][14][15][16][17][18]; this emphasizes the role of complexity in various geometries. It is interesting to note that issues related to complexity have been investigated in generalised gravity theories including Einstein-Gauss-Bonnet theory, the more general Lovelock theory, f(R) theory and other extended theories of gravity [6,[19][20][21][22][23][24].…”
Section: Previous Workmentioning
confidence: 99%
“…results from the causality conditions 0 ≤ V 2 r ≤ 1 and 0 ≤ V 2 t ≤ 1. Moreover, the equation( 50) can be explicitly interpreted as [72]:…”
Section: A Herrera's Cracking Conceptmentioning
confidence: 99%
“…Note that the idea of complexity may be applied to extended theories of gravity [11,12]. Recently Jasim et al [13] showed that a strange star in Einstein-Gauss-Bonnet gravity can be developed which is consistent with complexity. A general geometric concept that may also be used to study relativistic self-gravitating fluids is a symmetry on the manifold.…”
Section: Introductionmentioning
confidence: 96%